2016
DOI: 10.1130/b31482.1
|View full text |Cite
|
Sign up to set email alerts
|

An Antarctic stratigraphic record of stepwise ice growth through the Eocene-Oligocene transition

Abstract: Earth's current icehouse phase began ~34 million years ago with the onset of major Antarctic glaciation at the Eocene-Oligocene Transition (EOT). Changes in ocean circulation and a decline in atmospheric greenhouse gas levels were associated with step-wise cooling and ice growth at southern high latitudes.The Antarctic cryosphere plays a critical role in the ocean-atmosphere system, but its early evolution is still poorly known. With a near-field record from Prydz Bay, Antarctica, we demonstrate that Antarctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 92 publications
(144 reference statements)
3
74
0
Order By: Relevance
“…Higher-resolution modelling and better representation of climate feedbacks offer some potential improvements in this regard (Huber and Caballero, 2011;Baatsen et al, 2018), and the current Deep-MIP modelling effort might provide further insights into the causes of this common model bias. It should also be noted that these simulations were run with relatively arbitrary pCO 2 levels (although they are of a plausible magnitude; Pearson et al, 2009;Pagani et al, 2011;Foster et al, 2017), and these could be refined to provide a slightly better absolute fit to the data. Orbital variability does not appear to have a major impact on the comparison, as shown by the relatively minor impact on the results in the FOAM simulations and due to the length of the averaged periods of the proxy records.…”
Section: Discrepancies and Uncertainty In The Latitudinal Temperaturementioning
confidence: 99%
“…Higher-resolution modelling and better representation of climate feedbacks offer some potential improvements in this regard (Huber and Caballero, 2011;Baatsen et al, 2018), and the current Deep-MIP modelling effort might provide further insights into the causes of this common model bias. It should also be noted that these simulations were run with relatively arbitrary pCO 2 levels (although they are of a plausible magnitude; Pearson et al, 2009;Pagani et al, 2011;Foster et al, 2017), and these could be refined to provide a slightly better absolute fit to the data. Orbital variability does not appear to have a major impact on the comparison, as shown by the relatively minor impact on the results in the FOAM simulations and due to the length of the averaged periods of the proxy records.…”
Section: Discrepancies and Uncertainty In The Latitudinal Temperaturementioning
confidence: 99%
“…A number of studies have suggested there was cooling in the several million years prior to the EOT, particularly at high latitudes (e.g. Raine & Askin, 2001;Petersen & Schrag, 2015;Passchier et al, 2016;Carter et al, 2017;Pound & Salzmann, 2017). Even in the high Northern Hemisphere changes have been identified occurring prior to the EOT (e.g.…”
Section: Changes In the Latitudinal Temperature Gradientmentioning
confidence: 99%
“…Significant swings in global temperature thus occurred prior to the EOT. Yet, conditions only allowed the growth of a continental-scale Antarctic ice sheet after 34Ma, although indications for significant ice volume in the late Eocene have been 40 found (Scher et al, 2014;Passchier et al, 2017;Carter et al, 2017). It remains a question to what extent continental geometry (e.g.…”
Section: Introductionmentioning
confidence: 99%